Evaluating Library Collection Utilization Based on ISO 11620:2014: A Pilot Study at Slamet Riyadi University - Insan Elia Ivanka; Luthfi Maulia Ikhsan; Titin Sri Hartini; Valen Meilani Putri; Devi, Katrin Setio (Universitas Wijaya Kusuma Surabaya, 2026)
Purpose Research. This study evaluates collection utilization at the UNISRI Library using ISO 11620:2014 and describes factors related to collection availability and library services in the use of printed and electronic collections. The study is important for supporting evidence-based collection evaluation and service improvement in higher education libraries. Research Method. This study employed a descriptive quantitative pilot design by combining library automation system (SLiMS) data on visits and circulation with a questionnaire administered to 30 student users of the UNISRI Library. Analysis Data. The data were analyzed using descriptive statistics and interpreted based on selected ISO 11620:2014 indicators covering collection utilization, collection availability, and library service performance. Results. The findings show a utilization gap: library visits were relatively high, but borrowing and the use of electronic collections remained low to moderate. Printed collections were generally perceived as relevant and sufficiently current, and library services were rated positively. However, collection utilization was constrained by item unavailability, difficulties using the OPAC, ineffective search and retrieval, and metadata-related problems in accessing electronic resources. Conclusions. Collection utilization at the UNISRI Library remains limited despite positive perceptions of collection relevance and service quality, indicating that availability management and discovery and access systems remain key constraints. Improving utilization therefore requires better access tools, stronger metadata quality, and more targeted user guidance. Further research should involve a larger sample and a longer observation period. Keywords: Collection Utilization; Academic Library; ISO 11620:2014; Library Performance; Electronic Collections